2015
DOI: 10.1021/acs.est.5b00686
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Sources Contributing to Urban Air Pollution Using Adjoint Sensitivity Analysis: Benzene and Diesel Black Carbon

Abstract: The adjoint of the Community Multiscale Air Quality (CMAQ) model at 1 km horizontal resolution is used to map emissions that contribute to ambient concentrations of benzene and diesel black carbon (BC) in the San Francisco Bay area. Model responses of interest include population-weighted average concentrations for three highly polluted receptor areas and the entire air basin. We consider both summer (July) and winter (December) conditions. We introduce a novel approach to evaluate adjoint sensitivity calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Numerous studies have performed top-down estimations of CO 2 emissions using observations from urban surface monitoring networks of various sizes (e.g., Gratani and Varone, 2005;McKain et al, 2012;Newman et al, 2013;Lauvaux et al, 2013;Bréon et al, 2015;Turnbull et al, 2015). However, it is not immediately clear how many sites are necessary to monitor the emissions from an urban area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have performed top-down estimations of CO 2 emissions using observations from urban surface monitoring networks of various sizes (e.g., Gratani and Varone, 2005;McKain et al, 2012;Newman et al, 2013;Lauvaux et al, 2013;Bréon et al, 2015;Turnbull et al, 2015). However, it is not immediately clear how many sites are necessary to monitor the emissions from an urban area.…”
Section: Introductionmentioning
confidence: 99%
“…Yet most current urban monitoring networks have fewer than eight sites but operate for much longer than 8 weeks. For example, Gratani and Varone (2005) used a single site in Rome, Newman et al (2013) used a single site in Los Angeles, Lauvaux et al (2013) used two sites in Davos, Switzerland, McKain et al (2012) used a network of five sites in Salt Lake City, and Bréon et al (2015) used five sites in Paris. Recent work from Turnbull et al (2015) employed a denser network of 12 sites in Indianapolis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis found that a maximum number of premature deaths (approximately 8 000) are attributed to road emissions in California, while road emissions in Georgia result in approximately 1 500 premature deaths. Bastien et al [38] used the CMAQ adjoint model at a 1 km horizontal resolution to perform source attribution of ambient BC and benzene concentrations in the San Francisco Bay area. They found that the largest sensitivities with respect to emissions occur in the winter, with contributions from local sources of BC contributing between 62% and 85%.…”
Section: Introductionmentioning
confidence: 99%
“…While the work of Dedoussi and Barrett [37], Bastien et al [38], Lee et al [44], and Turner et al [39] utilized adjoint models to perform source attribution studies at high spatial, temporal, and sectoral resolutions, each study focused on health impacts across a large domain, such as the entire globe or the entire US. The extent to which emissions from individual locations and sources cause adverse health effects in specific urban areas has thus yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%